Analisis Pengaruh Relationship Marketing Terhadap Loyalitas Pelanggan pada Rumah Makan Asui Seafood di Kota Pangkalpinang - Ary Fakturrachman Aryansyah; Indah Novianti (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2025)
This study aims to assess the influence of relationship marketing on customer loyalty at Asui Seafood Restaurant, located in Pangkalpinang City. The research is motivated by the intensifying competition within the culinary sector, especially in Pangkalpinang, which has been recognized as one of Indonesia’s Creative Cities. Relationship marketing in this context involves fostering long-term connections with customers through components such as trust, commitment, communication, conflict resolution, and customer satisfaction. A survey method was employed, involving 120 customers of Asui Seafood Restaurant. Data analysis was carried out using SmartPLS version 3.2.8. The results reveal that relationship marketing significantly affects customer loyalty, with trust and satisfaction identified as the most influential factors. These findings offer valuable insights for culinary entrepreneurs in formulating effective relationship marketing strategies to enhance customer loyalty and improve competitive advantage